Expansion of a core regulon by transposable elements promotes Arabidopsis chemical diversity and pathogen defense - Brenden Barco (Nature Portfolio, 2019)
Arabidopsis plants can produce 4-hydroxyindole-3-carbonitrile (4OH-ICN) upon pathogen infection. Here, the authors show that EPCOT3, a retrotransposonderived enhancer, mediates WRKY33-binding, pathogen-responsive transcription of CYP82C2, and synthesis of 4OH-ICN.